Emotional neglect in childhood shapes social dysfunctioning in adults by influencing the oxytocin and the attachment system: results from a population-based study - Müller, Laura Elisa; Bertsch, Katja; Bülau, Konstantin; Herpertz, Sabine; Buchheim, Anna (International journal of psychophysiology, 2019)
Early life maltreatment (ELM) is the major single risk factor for impairments in social functioning and mental health in adulthood. One of the most prevalent and most rapidly increasing forms of ELM is emotional neglect. According to bio-behavioral synchrony assumptions, the oxytocin and attachment systems play an important mediating role in the interplay between emotional neglect and social dysfunctioning. Therefore, the aim of the present study was to investigate whether fear and avoidance of social functioning, two important and highly prevalent facets of social dysfunctioning in adulthood, are shaped by emotional neglect, plasma oxytocin levels and attachment representations. We assessed emotional neglect as well as other forms of ELM with the Childhood Trauma Questionnaire, current attachment representations with the Adult Attachment Projective Picture System, and fear and avoidance of social situations with the Liebowitz Social Anxiety Scale in a population-based sample of N=121 men and women. Furthermore, 4.9ml blood samples were drawn from each participant to assess peripheral plasma oxytocin levels. Applying a sequential mediation model, results revealed that emotional neglect was associated with lower plasma oxytocin levels which in turn were associated with insecure attachment representations which were related to elevated fear and avoidance of social situations (a1d21b2: F3,117=20.84, P<.001). Plasma oxytocin and current attachment representations hence fully and sequentially mediate the effects of emotional neglect on social fear and avoidance, two important facets of adult social dysfunctioning, confirming bio-behavioral synchrony assumptions.